2023
DOI: 10.1051/e3sconf/202338905042
|View full text |Cite
|
Sign up to set email alerts
|

Effective organization of technologies for speeding up freight transportation in railway transport

Abstract: The modern measures necessary to elihourate the stopping of cars during the delivery of cargo have been analyzed the regulatory and legal framework for the delivery of goods by rail. A mathematical model was developed for the relationship between the daily run of wagon consignments and the distance of transportation on the basis of drawing up a technological scheme that takes into account the entire sequence of operations performed with wagons along the route. This made it possible to deterhoure the impact of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 10 publications
0
0
0
Order By: Relevance
“…Every station has many pairs of control points installed on the approach section. It is found that the intervals between these locations correspond to the electrical centering system's mode entry times [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. When the rolling stock approaches the station, the first of the two control points notifies the interlocking system.…”
Section: Time Indicators For Automatic Preparation Of Routes For Trai...mentioning
confidence: 99%
See 1 more Smart Citation
“…Every station has many pairs of control points installed on the approach section. It is found that the intervals between these locations correspond to the electrical centering system's mode entry times [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. When the rolling stock approaches the station, the first of the two control points notifies the interlocking system.…”
Section: Time Indicators For Automatic Preparation Of Routes For Trai...mentioning
confidence: 99%
“…The length of the approach section to prepare routes for high-speed trains with speeds of 108-350 km/h in straight traffic is calculated using the following expression (12)…”
mentioning
confidence: 99%